If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -6x + -16 + -20x = 7 + -9x Reorder the terms: 3 + -16 + -6x + -20x = 7 + -9x Combine like terms: 3 + -16 = -13 -13 + -6x + -20x = 7 + -9x Combine like terms: -6x + -20x = -26x -13 + -26x = 7 + -9x Solving -13 + -26x = 7 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -13 + -26x + 9x = 7 + -9x + 9x Combine like terms: -26x + 9x = -17x -13 + -17x = 7 + -9x + 9x Combine like terms: -9x + 9x = 0 -13 + -17x = 7 + 0 -13 + -17x = 7 Add '13' to each side of the equation. -13 + 13 + -17x = 7 + 13 Combine like terms: -13 + 13 = 0 0 + -17x = 7 + 13 -17x = 7 + 13 Combine like terms: 7 + 13 = 20 -17x = 20 Divide each side by '-17'. x = -1.176470588 Simplifying x = -1.176470588
| 2(2-x)=9x-84 | | 22-4(-13)=12(-13)+126 | | M+6=-2m+6 | | (7x+4)-(24x-15)=180 | | 0.2(z+15)=3 | | 0.4x-1.2=0.15x+1.8 | | n(n-1)(n-2)(n-3)-84=0 | | y^4+26y^3+169y^2-900=0 | | h=-5 | | 15+8x=45+6x | | 11-6n=29 | | (3k+5)(-k)= | | 3(4x-4)+52=6x+4 | | 5x+1=6x+17 | | 3x+52=80 | | 2015=101b+19a | | 3c-7=-3+1 | | 47=47-8(5-1w) | | 2y=3y+19 | | 4x-2=2x+x+4 | | 1v+1=1v-6 | | 4(8+m)= | | -8+x+6=2x+x | | A(w-3)+5=3(w-1) | | 6r-1+6=6r | | 8x^2-16x-80=1 | | -5-(15y-1)=2(17-16)-y | | -8.0a-8=0.2a | | 3x+4+4x+6x-11+5x-7=85 | | -6x-4=-52 | | 90=4y+10 | | 5x^2-16x-340=0 |